Pengaruh Model Pembelajaran Talking Stick terhadap Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas VIII di SMP Negeri 1 Balige Kabupaten Toba Tahun Pembelajaran 2024/2025 - Hisar R. Panjaitan; Dame Taruli Simamora; Baginda Sitompul; Senida Harefa; Robert K.A. Simangunsong (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
The purpose of this study was to determine the effect of the Talking Stick Learning Model on Student Learning Activity in the Subject of Christian Religious Education and Character Education for class VIII at SMP Negeri 1 Balige, Toba Regency in the 2024/2025 Academic Year. The research hypothesis is: "there is an effect of the Talking Stick Learning Model on Student Learning Activity in the Subject of Christian Religious Education and Character Education for class VIII at SMP Negeri 1 Balige, Toba Regency in the 2024/2025 Academic Year". The population was all students of class VIII of SMP Negeri 1 Balige, Toba Regency in the 2024/2025 Academic Year who were Protestant Christians totaling 173 people. The research sample was determined using a purposive sampling technique, namely 30 students of class VIII B. This research method uses a quantitative research method with a pre-experimental design type in the form of "one shot case study". The instrument used in this study was a questionnaire item for variable Y totaling 18 items. Based on the experiments that have been carried out, the results obtained before treatment produced an average of 48.10 and after treatment 57.53. The research data for the questionnaire were analyzed using the One-Shot Case Study t-test formula. From the calculation results, the t-value = 3.599> t-table (α = 5%) = 2.042 was obtained. The t-value is in the area of ​​the H0 rejection curve and Ha acceptance. Thus, it can be concluded that with the difference between before and after treatment and t-value> t-table, the research hypothesis is accepted, namely that there is an influence of the Talking Stick Learning Model on Student Learning Activity in Christian Religious Education and Character Education subjects for class VIII at SMP Negeri 1 Balige, Toba Regency, in the 2024/2025 Academic Year.